Comment on "The Molecular Evolutionary Patterns of the Insulin/FOXO Signaling Pathway". (January 2013) - Alvarez-Ponce, David; Aguadé, Montserrat; Rozas, Julio
Letter to the Editor on Wang M, Wang Q, Wang Z, Zhang X, Pan Y. The molecular evolutionary patterns of the insulin/FOXO signaling pathway. Evol Bioinform . 2013;9:1–16. doi: 10.4137/EBO.S10539.